Optimizing Addition of Africal Catfish to the Level of Preferences and Nutritional Content of Cassava Rengginang - Maria, Tri Anna; Arsil, Yuliana; Rahayu, Dewi; Yolahumaroh, Yolahumaroh; Muharni, Muharni (JURNAL PROTEKSI KESEHATAN, 2024)
Rengginang cassava has a high carbohydrate content while the protein content is low so it is necessary to add other ingredients such as the addition of catfish. This type of research is an experimental study with a completely randomized design (CRD) consisting of four treatments, namely 0% (control), 10%, 20% and 30%, and using 25 semi-trained panelists. Based on the results of the highest average level of preference for the color, aroma, taste and texture of cassava rengginang with the addition of Africancatfish at aconcentration of 10%. The One-Way Anova test indicated a significant effect (р<0,05) in terms of color, aroma, taste, and texture. This study provides an innovation in traditional rengginang products by adding dumbo catfish as an additional protein source. This innovation transforms rengginang from merely a carbohydrate source into a highly nutritious snack rich in protein.